Government loan in the conditions of Ukraine’s new challenges - Харабара, Віолетта; Грешко, Роман Ігорович; Харабара, Володимер (Politics & Security, 2022)
The article substantiates the need for public lending to cover the state budget deficit at the present stage, examines the current state of Ukraine's public debt and analyzes main indicators of Ukraine's debt security.
Keywords: state credit; government borrowing; military bonds; budget revenues; budget expenditures, grant funds